Optegnelser af Mina Grundtvig den 4. august 1856 - Toldberg, Helge (Grundtvig-studier, 1948)
Mina Grundtvig’s jottings, 4/8 1856. We have here the text of an account written on 4/8 1856 by Grundtvig’s daughter-in-law Mina (daughter of his friend Prof. Stenersen and wife of his eldest son Johan) of a conversation which she had with Grundtvig a month earlier, based on brief notes which she took at the time. It has been presented to the Grundtvig Society by Grundtvig’s grandson, Vilhelm Grundtvig, former Librarian of Statsbiblioteket at Aarhus, and edited with explanatory notes by Steen Johansen, M. A. At the time of the conversation, Grundtvig was passing through a period of depression after the death of his second wife, and both he and those around him thought that his end was near. This may have been the reason for Mina’s asking him to tell her the story of his life. Her jottings give us an account of his career in the Church from the time of his ordination until his appointment to Vartov. There are some minor errors with regard to dates, etc., which are pointed out in the explanatory notes; but about some incidents the jottings give us fuller information than is available elsewhere. For instance, they give a detailed account of the audience with the King at which Grundtvig expressed his wish to go to England to study Anglo-Saxon and the King promised to help him. At first the King reproved him severely for not keeping the peace with the other clergy, but when Grundtvig asked, “ But is your Majesty sure that it is I who cannot keep the peace?” he answered, “ No, no — that is true” , and changed the subject. We are also given fresh details of the interview with Bishop Mynster on New Year’s Eve, 1838, when Grundtvig asked for permission to confirm his sons, and Mynster harshly answered, “ Do you think we can give every giddy curate leave to confirm?” We are told of Grundtvigs depression as he returned from the interview through the King’s Garden in the clear starlit night, but not of the sudden change to a more hopeful mood which expressed itself in his beautiful poem “ New Year’s Eve” .